R&D Cooperation between Universities and Enterprises - Barta, Györgyi; Csizmadia, Zoltán; Deák, Csaba; Dőry, Tibor; Kiss, Anett; Lengyel, Balázs (Discussion Papers, 2012)
From the second half of the 20th century, organised cooperation between universities and enterprises became an essential factor in R&D. Globalisation helped open a new chapter of R&D with the organisational fragmentation of R&D as an important feature: multinational companies began to relocate part of this activity in other well developed and less developed countries. In addition, governments are increasingly willing not only to support but also to participate in R&D cooperations (known as the “triple helix model”). As a consequence, an open system of international innovation has evolved. For Hungary as one of the post-transition economies it is vitally important to find ways to participate in the worldwide innovation process. The new situation allows universities and enterprises in the less developed countries, too, to be actors in this process. Earlier research and dedicated literature deal mainly with the relationship between foreign large companies, multinationals and local universities in the field of R&D. However, this is only one element of R&D cooperation. To create a stable and concrete mutual interest between universities and the economy has become a general goal. There are numerous obstacles – legal, financial, economic, etc. – which hinder the formation of a university–enterprise relationship. The scope of our empirical study is particular in that it explores the long-term effect of those important R&D cooperation that had already ended. The purpose of the study was to examine whether the working connections developed among the partners survived the end of large projects, continued later and could be utilised for new purposes. For the network capital thus created carries a large value, particularly if the local possibilities are limited (for example, if only one local university and a few companies can be found in one region). If this research can demonstrate the positive influence of large projects initiated and funded by state agencies, it would help to justify and encourage governmental support in R&D. In the first part of the study, we deal with the history of cooperation between the universities and companies, the different types of their relationship, the cases of developed and less developed countries; the special situation in Hungary after the change of the political system; and the characteristics of the partners involved (foreign and domestic enterprises and the local universities). The second part describes the empirical study: the purpose and scope of the study, the details and results of our research, and the potential practical use of the results.